A reflection of national integration process and the role of media in Malaysia - Chang, Peng Kee; Kho, Suet Nie (Penerbit Universiti Kebangsaan Malaysia, 2017)
National integration is an on-going process in Malaysia since independence. Media are found to play an important role to enhance the process, especially in disseminating government policies. After independence, the biggest task entrusted to the government of Malaysia was to integrate the different races together without taking away the ethnic identity of the races. The integration process reached a breaking and turning point during the incident of May 13, 1969 the bloody riot caused by racial tension. The government became more diligent and the media became one of the machinery by which the government continued to work on nation building and the integration of different races. One policy was implemented after another, from National Cultural Policy; New Economic Policy and the Rukun Negara. Revamp of education policies and the setting up of National Unity Department in the Ministry Of National Unity And Social Development was some of the major milestones in national integration. This conceptual paper is a reflection of the past policies and emulation of the present 1Malaysia roadmap for national integration. It started out by defining the different means by which national integration can be achieved such as through the process of assimilation, integration and pluralism. It then took steps back by reflecting on old national integration policies and the prominent role of the media in it over the years. The paper also reflects on the recent 1Malaysia roadmap, press freedom in Malaysia and how it affects the national integration process.